Age‐associated microRNA expression in human peripheral blood is associated with all‐cause mortality and age‐related traits. Issue 1 (17th October 2017) - Huan, Tianxiao; Chen, George; Liu, Chunyu; Bhattacharya, Anindya; Rong, Jian; Chen, Brian H.; Seshadri, Sudha; Tanriverdi, Kahraman; Freedman, Jane E.; Larson, Martin G.; Murabito, Joanne M.; Levy, Daniel
Summary: Recent studies provide evidence of correlations of DNA methylation and expression of protein‐coding genes with human aging. The relations of microRNA expression with age and age‐related clinical outcomes have not been characterized thoroughly. We explored associations of age with whole‐blood microRNA expression in 5221 adults and identified 127 microRNAs that were differentially expressed by age at P  <   3.3 × 10 −4 (Bonferroni‐corrected). Most microRNAs were underexpressed in older individuals. Integrative analysis of microRNA and mRNA expression revealed changes in age‐associated mRNA expression possibly driven by age‐associated microRNAs in pathways that involve RNA processing, translation, and immune function. We fitted a linear model to predict 'microRNA age' that incorporated expression levels of 80 microRNAs. MicroRNA age correlated modestly with predicted age from DNA methylation ( r  =   0.3) and mRNA expression ( r  =   0.2), suggesting that microRNA age may complement mRNA and epigenetic age prediction models. We used the difference between microRNA age and chronological age as a biomarker of accelerated aging (Δage) and found that Δage was associated with all‐cause mortality (hazards ratio 1.1 per year difference, P  =   4.2 × 10 −5 adjusted for sex and chronological age). Additionally, Δage was associated with coronary heart disease, hypertension, blood pressure, and glucose levels. In conclusion, we constructed a microRNA age prediction model based on whole‐blood microRNA expression profiling. Age‐associated microRNAs and their targets have potential utility to detect accelerated aging and to predict risks for age‐related diseases.